Determinants of 20‐year non‐progression to Type 2 diabetes in women at very high risk: the E3N cohort study. Issue 12 (19th July 2018) - Fagherazzi, G.; Gusto, G.; Mancini, F. R.; Dow, C.; Rajaobelina, K.; Balkau, B.; Boutron‐Ruault, M.‐C.; Bonnet, F.
Abstract: Aims: To identify the most important determinants associated with not developing Type 2 diabetes in women considered to be at very high risk. Methods: Between 1995 and 2014, we followed 402 women from the E3N cohort study who were considered to be at very high risk of Type 2 diabetes based on the D.E.S.I.R. score. We then computed a classification and regression tree model to identify, among a large set of risk factors, the top risk factors associated with not having Type 2 diabetes at the end of the follow‐up. Results: During follow‐up, 117 women (29%) were diagnosed with Type 2 diabetes, while 285 (71%) were still free of the disease in 2014. A low Western dietary pattern score was the top characteristic associated with not developing Type 2 diabetes, as only 20% of the women at very high risk in the E3N study with that characteristic developed Type 2 diabetes (compared with 29% overall). In women with a moderate or high Western dietary pattern score, the most important characteristic associated with not developing Type 2 diabetes was a high total dietary antioxidant capacity, as only 26% of these women ultimately developed Type 2 diabetes. Conclusions: We showed that the top characteristic associated with not developing Type 2 diabetes, despite being at very high risk, was a healthy diet, characterized by limiting Western dietary habits, but with a high intake of antioxidant‐rich foods. This underscores the importance of diet in the prevention of Type 2 diabetes in people at high risk. What's new?: Dietary habits play a major role in diabetes prevention in people at risk of Type 2 diabetes. The top characteristic found to be associated with not developing Type 2 diabetes was the limiting of foods typical of a Western diet [in the present study population, essentially processed meat, French fries, appetizers (olives, crackers, peanuts, almonds, hazelnuts, pistachios, walnuts), rice/pasta, potatoes, pulses, pizza/pies, canned fish, eggs, alcoholic beverages, cakes, mayonnaise, and butter/cream]. The second most important characteristic was a high intake of antioxidant‐rich foods (such as coffee, tea, fruit and vegetables, and chocolate). Our results provide evidence to aid the design of new intervention and prevention strategies in individuals at very high risk of Type 2 diabetes.